An evaluation for sustainable mobility extended by D numbers - Mo, Hongming; Deng, Yong (Technological and Economic Development of Economy, 2019)
How to evaluate the impact of transport measures on city sustainability effectively is still an open issue, and it can be abstracted as one of the multiple criteria decision making problems. In this paper, a new method based on D numbers is proposed to evaluate the sustainable mobility of city. D number is a new mathematical tool to represent and deal uncertain information. The property of integration of D numbers is employed to fusion information. A numerical example of carsharing demonstrates the effectiveness of the proposed method. First published online 31 May 2019